(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction: Endodontically Treated Teeth (ETT) may experience a decrease in mechanical strength, leading to increased fragility and susceptibility to fractures primarily caused by the loss of tooth structure integrity when restoring ETT. It’s important to consider the (remaining tooth structures, tooth position, occlusal forces, and aesthetics) which typically requires the use of a traditional post and core foundation along with a crown or endocrown system. The purposes of this study to determine prevalence and preference for use of endocrown and conventional crown in endodontically treated teeth and to assess knowledge, including comparisons of endocrown and conventional crown, in endodontically treated teeth among Saudi Arabia dentists. Methodology: This study is of a cross-sectional design, conducted in Saudi Arabia from July to November 2024. Through social media platforms like Twitter, WhatsApp, Telegram, Instagram and Snapchat, this study attempts to recruit participants. Included were dental practitioners from all provinces of the Kingdom of Saudi Arabia, who performed endocrown and conventional crowns in their practice, and dentists willing to participate in the study and filled a detailed questionnaire. Dentists who have had neither experience with endocrown nor conventional crowns were excluded as criteria. Results: The finding of significant insights in the knowledge and awareness of endocrown vs conventional crowns in endodontically treated teeth are highlighted in this cross-sectional study of 517 dentists in Saudi Arabia. We found that 89.2% of participants were aware of endocrown; however, 75% of participants showed low knowledge levels of endocrown application. Endocrown were considered less conservative by 79.7% of respondents, who however expressed concern about technique sensitivity and possible complications. While 60.5 percent agreed to conventional crowns, 60.5 percent endorsed endocrown, reflecting a growing use of the latter. Practice area, practitioner type, and years of experience were significantly related to awareness, and areas of educational improvement are highlighted. Conclusion: Though, this study demonstrates a high awareness of the use of endocrown among Saudi dentists, they also indicated the lack of knowledge regarding their applications. Endocrown are being adopted while it is still preferred to have the conventional crown, but little change from traditional practices is occurring due to familiarity and fear of complications. Enhanced educational initiatives are essential to bridge this knowledge gap, ultimately improving clinical practices in endodontics across Saudi Arabia.